Communicating change : how to win employee support for new business directions - Larkin, T. J. (McGraw-Hill New YorkUS, 1994)
Suggests that direct communication between senior management and supervisors; face-to-face communication; and, communication of the relevant performance of the work area, are the best ways to communicate change to employees in large companies. Bases these suggestions on the theories that communication should be receiver-oriented; and should change behaviour. Warns against senior management communicating directly to frontline workers, and discusses strategies for improving communication between middle managers and frontline employees.